Asymmetric capacitive deionization utilizing nitric acid treated activated carbon fiber as the cathode. (10th September 2015) - Wu, Tingting; Wang, Gang; Dong, Qiang; Qian, Bingqing; Meng, Yulan; Qiu, Jieshan
Graphical abstract: Highlights: A low-cost asymmetric capacitive deionization cell was established. Commercial activated carbon fiber was simply treated by nitric acid and used as the cathode. Influences of cathode modification on removal capacity and charge efficiency were thoroughly investigated. High removal capacity (12.8 mg/g), improved charge efficiency (above 65%) and good cycling stability were obtained. Abstract: In capacitive deionization (CDI), co-ions will be repelled simultaneously from the electrodes when counterions are adsorbed onto the electrodes, leading to a diminished CDI performance. To reduce this so-called co-ion effect, carboxylic groups were grafted onto the surface of commercial activated carbon fiber (ACF) using a simple nitric acid treatment (ACF-HNO3 ). ACF-HNO3 exhibited good cation selectivity. An asymmetric CDI cell (N-CDI) was assembled, in which ACF-HNO3 was used as the cathode and pristine ACF as the anode. The removal capacity of N-CDI at 1.2 V can be as high as 12.8 mg/g, whereas that of the symmetric CDI cell composed of pristine ACF (0-CDI) is only 8.0 mg/g. Accordingly, the charge efficiency of N-CDI stays above 74%, whereas that of 0-CDI is below 40% at various applied voltages. Moreover, N-CDI exhibited better cyclic stability than 0-CDI. These results indicate that use of ACF-HNO3 as the cathode can effectively reduce co-ion expulsion, thereby enhancing the CDI performance.